Scaling peer-to-peer games in low-bandwidth environments - Pang, Jeffrey; Uyeda, Frank; Lorch, Jay (Proceedings of the 6th International Workshop on Peer-to-Peer Systems (IPTPS), 2007)
In peer-to-peer multiplayer games, each peer must send periodic updates of its objects to other peers. Since typical broadband users have little upload bandwidth, updates to each player will be infrequent when there are many players in the game. This leads to choppy and unsatisfying gameplay. Therefore, we propose three techniques to compensate for low upload bandwidth in peer-to-peer games: focus sets, pairwise rapid agreement, and guidable AI. To test these techniques, we implement them and conduct a user study that evaluates the resulting game. We find that our techniques make a game played with low bandwidth significantly more fun than existing techniques, and nearly as much fun as one played on a LAN. Thus, they enable an order of magnitude more players than existing techniques.